Pengaruh Media Sosial Grup Whatsapp ”Iwak” terhadap Interaksi Sosial Masyarakat RT/RW 001/002 Desa Tisnogambar Kecamatan Bangsalsari Kabupaten Jember - Rofiatun Hasanah; Ferdian Ardani Putra; Abdul Latif Najmuddin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The development of information technology has brought significant changes in various aspects of people's lives. One platform that has experienced rapid development and is used by almost all levels of society is WhatsApp. This application has become the main means of communication, both in personal and social contexts. This study focuses on the influence of WhatsApp social media on community social interactions with the aim of determining how much influence WhatsApp social media has on community social interactions, especially in Tisnogambar Village RT/RW 001/002, Bangsalsari District, Jember Regency. The research method used is quantitative research with data collection techniques through observation, questionnaires distributed directly to respondents, and documentation. Data analysis was carried out statistically by processing data using the SPSS 25 application. The results of the study based on the hypothesis test showed that the t-count value was greater than the t-table, namely 3.983 > 1.999 with a significance value of 0.000 < 0.05. The conclusion of this study shows that WhatsApp social media has a significant influence on community social interactions. This shows that the more intense the use of WhatsApp, the more social interactions in society also experience changes.